POLA PEMBINAAN ANAK DIDIK PEMASYARAKATAN DI LEMBAGA PEMBINAAN KHUSUS ANAK KELAS I KUTOARJO - Andriyana, Narvedha (Jurnal Komunikasi Hukum (JKH), 2020)
Children are the future of the nation that must be protected and fulfilled all their rights. Even though the child is carrying out training at LPKA and automatically loses their freedom of movement, the child still gets all his rights such as the right to education then the child also gets various kinds of training according to their interests and talents. The pattern of coaching carried out in LPKA Class I Kutoarjo is divided into 4 stages, namely the environmental introduction stage, the initial stage, the advanced stage and the final stage. This research The research method in this writing is normative juridical, namely based on statutory regulations. Where the laws and regulations used are in accordance with the title of this study. Normative legal research basically examines law in its form as a norm, as contained in statutory regulations. Primary legal materials are legal materials that are binding such as regulations and legislation, while secondary legal materials are legal materials that are supporting primary legal materials such as literature, published journal books, magazines, and newspapers. Children who are carrying out training at LPKA are expected to become individuals who change their mindset and behavior so that children can reintegrate into the community without having bad perspectives in society.